Web standards programmer's reference : HTML, CSS, JavaScript, Perl, Python, and PHP - Schafer, Steven M. (Programmer to programmer., 2005)
"Serving as both a "how-to" guide and a reference, this book is one-stop reading for all the essential Web standards - XHTML, CSS, JavaScript, CGI with Perl and Python, and PHP. In today's web environment, professional web coders and serious enthusiasts need to create documents and scripts that comply with published standards so your content can be viewed on as many web-capable platforms as possible. The book teaches the standards and technologies necessary to achieve that desired result." "Packed with examples for learning each of these standard technologies and followed by detailed references to each language, this book provides a total package for moving your web publishing to current standards-based coding."--Jacket